Le fondement démocratique du droit de décider des Catalans - Mercè Corretja Torrens (Cahiers de Civilisation Espagnole Contemporaine)
This article examines the transformation of the political concept “right to decide” into a true right based on the democratic principle. The article draws the outlines of the new right, distinguishing it from other related or similar concepts, like the right of self-determination of peoples or the theories of secession. The bearer of this new right is the individual, although the right is exercised jointly by a group of individuals. It can be defined as the right of the members of a territorial community which is democratically organized to redefine their political and institutional status, including the possibility of creating a new state by means of a negotiated process. This new right that has been recognized in some democratic plural states, could also find its anchorage in the Spanish Constitution of 1978. Finally, the prospect of initiating a process of remedial secession according to international law is explored, in case the exercise of the right to decide is blocked.